Konsep Pendidikan Anak Usia Dini Berdasarkan Al-Qur'an - Nir wana (EL-TARBAWI, 2020)
Early childhood education is an important stage to be prepared carefully and conceptually. The verses in the Koran can be used as a guide in providing the values of early childhood education in an Islamic way to face modern life today. This study aims to discuss early childhood education in the Koran, stages of early childhood education in the Koran, Surah Luqman, and the concept of early childhood education in the Koran, Surah Lukman. This research uses the literature study method. This study found that early childhood education has beneficial roles in life. This study also found seven stages of educating early childhood and six concepts of early childhood education in the Koran, Surat Luqman. A researcher hopes that this research can be useful for future research in the field of early childhood education from an Islamic perspective.